MODERN APPROACHES IN PRIMARY EDUCATION - Husniddin Temirov Muyassarovich (American Journals, 2022)
This article provides information about the importance of organizing lessons taking into account the age and capabilities of students and providing guaranteed knowledge in the process of using modern innovative methods.
Keywords: state educational standard, pedagogical technology, efficiency.